Marine biodiversity of Bahía Culebra, Guanacaste, Costa Rica: published records - Cortés, Jorge (Universidad de Costa Rica, 2012)
A survey of the published records of marine organisms of Bahía Culebra, an enclosed embayment on the north Pacific coast of Costa Rica, is analyzed resulting in a list of 577 species representing 22 phyla. The most diverse groups documented were crustaceans, cnidarians and mollusks in order of species number. The first published record of any marine organism from the area, a polychaete, occurred in 1922, with a peak of published records of species between 1940 and 1949 and, more recently, from 2000 to the present. Several additional taxa are known from the region but there are no published records of their occurrence. This is especially evident for such groups as the free living flatworms and black corals. Additionally, several habitats, including soft bottom sediments, have not been sampled. Because of the paucity of knowledge on the biodiversity of Bahia Culebra, much more research is needed in order to evaluate and understand the effect of climate change and increasing anthropogenic activities.